Meso-macro analysis of microwave-assisted double-indenter impact on rock-like materials - Peng WANG; Zhongwen YUE; Shengnan XU; Dan GAO; Meng REN; Akang LI; Weijun LIU (Meitan xuebao)
Given the constraints on explosives and in response to the national “dual carbon” strategic goals, a new method of microwave-assisted impact fragmentation of rock-like materials has broad prospects in hard-rock tunneling, concrete structure demolition, and other projects due to its environmental friendliness and strong rock-breaking capability. However, its internal mechanism remains unclear. This study takes grouted concrete as the research object and relies on the established macroscopic dual-indenter synchronous impact experimental system (DHPB) and mesoscopic scanning electron microscopy (SEM). Through theoretical derivation and experimental verification, it explores the variation laws of macro-specific energy consumption and meso-damage of concrete specimens under dual-indenter synchronous impact with different microwave radiation times, establishing a quantitative functional relationship between macroscopic specific energy consumption attenuation degree and mesoscopic damage mediated by critical strain energy density. The results show that microwave radiation-induced degradation of concrete mechanical properties exhibits threshold characteristics. When the strain energy density absorbed by the concrete is less than the strain energy density required for the initiation of crack propagation, there is essentially no damage within the concrete specimen. However, as the absorbed strain energy density increases, the damage to the specimen accumulates nearly linearly with the strain energy density. The mesoscopic crack propagation within the concrete specimen has instantaneous characteristics. With the increase of microwave radiation time, it first expands statically and then transitions to dynamic expansion. During the dynamic expansion process, the instantaneous release of a large amount of energy can cause the entire specimen to instantaneously break into small pieces. Microwave radiation can significantly affect the failure mode of concrete specimens under dual-indenter synchronous impact. Without microwave radiation, the final fracture path of the concrete specimen is basically consistent with the direction of the line connecting the dual indenters. With microwave radiation, the final fracture path forms a larger angle with the direction of the line connecting the dual indenters, and multiple macroscopic cracks may occur. The maximum value of macroscopic specific energy consumption of concrete specimens under microwave radiation is 0.69, and the corresponding mesoscopic damage is 0.68, both of which are basically consistent. This means that the increase in mesoscopic crack length and quantity can quantitatively reduce macroscopic specific energy consumption, revealing the internal mechanism by which microwave radiation weakens the impact resistance of rock-like materials. The research results provide a scientific basis for the application of microwave-assisted mechanical impact in engineering.